PROSES KREATIF SIDIK NUGROHO DALAM PENULISAN NOVEL TEWASNYA GAGAK HITAM - Egi Repomi; Christantosyam Christantosyam; Agus Wartiningsih (Universitas Tanjungpura, 2022)
AbstractThis study aims to describe the implementation is how Sidik Nugroho obtained the source of the idea, through the incubation process, pouring the idea of the novel Tewasnya Gagak Hitam, implementation in the form of text in Indonesian language learning related to Sidik Nugroho's creative process in writing the novel Tewasnya Gagak Hitam. The approach in this research is expressivism with the data collection technique is a documentary study technique. The data collection tool is the researcher as the key instrument assisted by writing instruments and research instruments. The data source of this research is Sidik Nugroho as the author of the novel Tewasnya Gagak Hitam with data in the form of video recordings of the results of the interview with Sidik Nugroho. The technique of testing the validity of the data used triangulation persistence and referential adequacy.The results showed that the creative process data of Sidik Nugroho in the writing of the novel Tewasnya Gagak Hitam were found to be 17 forms consisting of 6 forms of idea sources, 5 forms of incubation processes, and 6 forms of pouring ideas. The implementation plan for learning the results of this research is combined with Indonesian language learning in class X SMA/equivalent level in the 2013 curriculum with KD 3.14 Assessing things that can be imitated from biographical texts KD 4.14 Revealing things that can be imitated from the characters contained in the biographical texts read in writing.Keywords: Learning, Text Reviews, and Writing